Design, synthesis, and biological characterization of a potent STAT3 degrader for the treatment of gastric cancer - Haobin Li; Haobin Li; Lingling Wang; Lingling Wang; Fei Cao; Fei Cao; Dehua Yu; Jing Yang; Xuefei Yu; Jinyun Dong; Jinyun Dong; Jiang-Jiang Qin; et al. (Frontiers Media S.A., 2022)
Gastric cancer is a common malignant tumor that threatens human health, and its occurrence and development mechanism is a complex process involving multiple genes and multiple signals. Signal transducer and activator of transcription 3 (STAT3) has been elucidated as a promising target for developing anticancer drugs in gastric cancer. However, there is no FDA-approved STAT3 inhibitor yet. Herein, we report the design and synthesis of a class of STAT3 degraders based on proteolysis-targeting chimeras (PROTACs). We first synthesized an analog of the STAT3 inhibitor S3I-201 as a ligand, using the cereblon (CRBN)/cullin 4A E3 ligase ligand pomalidomide to synthesize a series of PROTACs. Among them, the SDL-1 achieves the degradation of STAT3 protein in vitro, and exhibits good anti-gastric cancer cell proliferation activity, inhibits invasion and metastasis of MKN1 cell, and induces MKN1 cell apoptosis and arrests cell cycle at the same time. Our study shows that SDL-1 is a potent STAT3 degrader and may serve as a potential anti-gastric cancer drug, providing ideas for further development of drugs for clinical use.